A case report of large vesico-vagino-rectal fistula with a large stone within fistula - A Ali Ramaji (Babol University of Medical Sciences, 2002)
Background and Objective: Pelvic surgery, radiation, cancer of cervix and trauma due to vesicovaginorectal fistula. There are different treatments depending on the size of fistula and also factors that cause occurring this disease. In some rare cases, this fistula can extend and involve the rectal wall and cause vesicovaginorectal fistula. Case: A 55-year-old female patient referred with urinary incontinence because of prolonged difficult labor in 30 years ago. Five years after labor because of large fistula, ureters anastomosed to sigmoid colon (An unusual method). Paraclinical tests showed a large stone (10×10 cm) in all urethra, vagina and rectum. After bowel preparation, she was operated by a midline laparotomy incision and the stone was removed. Conclusion: Late complications of ureterosigmoidostomy are stenosis of ureter to sigmoid, cancer of rectum and stone formation. For this purpose, more follow up should be done after this type of operation.